Investigating the factors affecting utilitarian and Hedonic Shopping in Iran - Seyednajmaldin Mousavi, Abolfazl Alizadeh, Reza Sepahvand, Mahmoudreza Esmaili, (Opción, 2019)
The purpose of this study is to investigate the effect of factors affecting utilitarian and hedonic shopping. This research is applied, based on nature and method, is descriptive and from correlation type. One of the results of this research is that brand loyalty and brand sensitivity affects utilitarian shopping. As a conclusion, the price level and the value obtained from it affect the type of purchase of two cities, and we found that the two cities do not differ in the price level in the hedonic and utilitarian purchase.